Using collaborative model to examine online persuasion through e-commerce website design: Comparative study between Gen X and Gen Y online shoppers in Malaysia - Loh, Yin Xia (2021)
This study examined online persuasion through website design by using the Elaboration Likelihood Model (ELM) and Persuasive System Design (PSD). This study investigates the phenomenon of the success of Lazada and Shopee to provide guidelines for website designers and local sellers to enhance the e-commerce website’s persuasiveness. The persuasive design features in Lazada and Shopee e-commerce websites were evaluated based on the design criteria of the ELM and the PSD model. This study has examined (1) the influence of central route elements (Dialogue Support and Primary Task Support) towards Lazada and Shopee user s attitude change, (2) the influence of Lazada and Shopee user s attitude change towards behavioural intention and (3) the influence of Lazada and Shopee user s behavioural intention towards actual online buying behaviour. There are seven hypotheses proposed initially and tested through the online survey to achieve the research objectives. The relative’s differences between Generation X and Generation Y perception of e-commerce persuasiveness had been compared. The leading e-commerce platforms: Lazada and Shopee were selected as a case study. Overall, there were 432 respondents involved in this research where 73.2% from Gen Y and 26.8% from Gen X. The collected data were analysed using Partial Least Square Structural Equation Modelling (PLS-SEM) technique. The results from the analysis indicated that Primary task support through navigation design, (PTN) was found to be the most influential persuasive design criteria, followed by Social support through connectedness (SSC), and Dialogue support through argument quality (DSA). According to the results, H1, H2, H3, H4, H7 of the study were accepted. The findings indicated that there is no significant difference between Gen X and GenY except the influential of Credibility support through navigation design (CSN) element. CSN proved to be a strong predictor in Online Buying Attitude (ATT) among Gen X, which is in contrast with Gen Y. Lazada and Shopee should emphasise on the implementation of the liking design technique under DSA when targeting Gen X users. The tailoring design technique under PTN should be emphasised when targeting Gen Y users. Based on the study, it can be concluded that all objectives were achieved, and the validation of the collaborative model was done.